1993
DOI: 10.1148/radiology.186.1.8416550
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pulmonary CT: findings in healthy adult men.

Abstract: The authors examined 10 healthy male subjects with dynamic computed tomography to determine normal dynamic and expiratory findings. In both the supine and prone positions, the average increase in lung attenuation during exhalation was found to be significantly greater in dependent lung regions than in nondependent lung regions. In each of the lung zones studied, there was a significant correlation between the decrease in cross-sectional lung area during exhalation and the increase in lung attenuation. At the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
2
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(96 citation statements)
references
References 0 publications
6
86
2
2
Order By: Relevance
“…From 90% VC to 10% VC, the mean lung density increased by 80 HU in the upper zones of the lungs and 86 HU in the lower zones. This is much less than reported by WEBB et al [18], who found an increase in attenuation of 200 HU in healthy volunteers. Our numbers are more consistent with air-trapping and are a reflection of the study population, in which patients with COPD are well represented.…”
Section: Discussioncontrasting
confidence: 59%
“…From 90% VC to 10% VC, the mean lung density increased by 80 HU in the upper zones of the lungs and 86 HU in the lower zones. This is much less than reported by WEBB et al [18], who found an increase in attenuation of 200 HU in healthy volunteers. Our numbers are more consistent with air-trapping and are a reflection of the study population, in which patients with COPD are well represented.…”
Section: Discussioncontrasting
confidence: 59%
“…The relatively opaque normal lung willincrease in attenuation and decrease in volume, as expected [6]. In primary vascular lung disease, because there is no air trapping or airway disease, the attenuation of both the hyperemic and oligemic lung at inspiration will increase in a similar fashion, and the volume of both will pare the different regions of lung attenuation for changes between inspiration and expiration, but occasionally it will be helpful to quantitatively compare the Hounsfield measurements of lower-attenuation and higher-attenuation areas of lung in scans obtained at inspiration and at expiration (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…The question of the importance, or otherwise, of focal areas of low attenuation consisting of one or more secondary pulmonary lobules has persisted since such "abnormalities" were reported on dynamic expiratory CT in four out of 10 apparently healthy volunteers with normal pulmonary function tests [108]. Such areas of decreased attenuation are not usually present or conspicuous on inspiratory HRCTs of normal individuals [102] and, when identified, need to be distinguished from artefactual areas of low density caused by adjacent ribs (beam hardening artefact).…”
Section: Accuracy Of High-resolution Computed Tomography Signs and Inmentioning
confidence: 99%